The Impact of Blockchain Technology on Sharia Philanthropy: Enhancing Donation Transparency in Indonesia - Avid Leonardo Sari; Irwandi; Agusfian Saptayuda; Yesika Yanuarisa; Fitri Nurlaela (International Journal of Science and Society, 2025)
The development of Islamic philanthropy in Indonesia has shown significant growth along with growing public awareness of religious-based donation practices. However, this increase has not been fully accompanied by a uniform level of transparency and open reporting among Islamic philanthropic institutions. This situation presents challenges in building public trust, especially amidst increasing demands for accountability and access to information in the digital environment. This study aims to analyze the role of blockchain technology in increasing transparency in the management and reporting of donations in Islamic philanthropy in Indonesia. The research method used is a qualitative approach, reviewing various scientific literature, institutional reports, and academic publications relevant to the research topic. The results indicate that limitations in reporting systems and fragmented data management remain major obstacles to achieving transparency in Islamic philanthropy. The use of blockchain technology has the potential to strengthen the traceability of fund flows, the reliability of transaction recording, and the ongoing access to donation information for the public. Increased transparency through this technology-based system has implications for strengthening public trust, sustainable donor participation, and the institutional legitimacy of Islamic philanthropy in Indonesia.